2008
DOI: 10.1016/j.jmaa.2007.05.075
|View full text |Cite
|
Sign up to set email alerts
|

An extension of the incomplete beta function for negative integers

Abstract: The incomplete beta function B x (a, b) is defined for a, b > 0 and 0 < x < 1. Its definition can be extended, by regularization, to negative non-integer values of a and b. In this paper we define the incomplete beta function B x (a, b) for negative integer values of a and b. Further we prove that the function ∂ m+n ∂a m ∂b n B x (a, b) exists for m, n = 0, 1, 2, . . . and all a and b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…We first consider the integral For further results on the Beta function and the incomplete Beta function, see [3][4][5][6].…”
Section: Some Results On the Beta Function And The Incomplete Beta Fumentioning
confidence: 99%
“…We first consider the integral For further results on the Beta function and the incomplete Beta function, see [3][4][5][6].…”
Section: Some Results On the Beta Function And The Incomplete Beta Fumentioning
confidence: 99%
“…We use neutrix limit [9][10][11][12][13][14][15][16] to defne the frational derivatives for (1)- (6).…”
Section: Introductionmentioning
confidence: 99%
“…Fisher at al. used neutrices to define the gamma and beta function for all real values [4,5].Özçaḡ et al applied the neutrix limit to extend the definition of the incomplete beta function and its partial derivatives to negative integers, [11,12]. It was shown that the neutrix limit of the q-gamma function and its partial derivatives exist for all values, [13].…”
Section: Introductionmentioning
confidence: 99%